Pemanfaatan Business Intelligence sebagai Alat Pengambilan Keputusan dalam Kegiatan Trading Item In-Game pada Game Online - Apta Gustafausta, Arzenico; Emirul Bahar (Journal of Management and Bussines (JOMB), 2025)
This study aims to explore the use of Business Intelligence (BI) in making decisions about trading digital items in online games and identifying profit opportunities through virtual market data analysis. The research methods used include collecting historical price and sales volume data from the official platform (Steam Community Market), selecting popular items using the elimination method, and analyzing trends using Tableau for data visualization and processing. The results show that most items experience a decrease in price and sales volume from month to month. However, several items, such as the Head Shot skin (Covert – StatTrak – Factory New), show a significant price increase trend over a certain period. The conclusion of this study is that although the in-game trading market tends to be volatile, the application of Business Intelligence can identify items with profit potential and support more accurate, data-driven decision-making. Keywords: Business Intelligence, In-Game Trading, Data-Driven Decision Making, Tableau